Emerging and re-emerging infectious diseases in pregnant women in an amazonian region: a large retrospective study from French Guiana - Najeh Hcini; Véronique Lambert; Jean-François Carod; Meredith Mathieu; Gabriel Carles; Olivier Picone; Jeanne Sibiude; Leo Pomar; Mathieu Nacher (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Pulmonary Histoplasmosis in People Living with Human Immunodeficiency Virus in French Guiana: Clinical Epidemiology, Medical Imaging and Prognostic - Morgane Bourne-Watrin; Antoine Adenis; Gary Doppelt; Magaly Zappa; Loïc Epelboin; Mathieu Nacher; Jeanne Bigot; Kinan Drak Alsibai; Romain Blaizot; Denis Blanchet; Magalie Demar; Geneviève Guillot; et al. (Mycopathologia, 2023)
Background Histoplasmosis is mainly described as a disseminated disease in people living with HIV (PLHIV). Compared to historical descriptions in immunocompetent individuals, knowledge is lacking on the detailed clinical and radiological findings and outcomes of pulmonary histoplasmosis (PH). Overlooked or misdiagnosed with other AIDS-defining condition, prognostic of PLHIV may be at risk because of inappropriate care. Methods A retrospective multicentric study was conducted in PLHIV from French Guiana between January 1988 and October 2019. Proven PH were documented through mycological direct examination, culture, or histology. Patients with concomitant respiratory infections were excluded. Results Among 65 patients, sex ratio M:F was 2.4 with a median age of 39 years [IQR 25–75%: 34–44]. Median CD4 count was 24 cells/mm 3 [11–71], with histoplasmosis as the AIDS-defining condition in 88% and concomitant AIDS-defining conditions in 29%. Clinical findings were fever (89%), cough (58%), dyspnea (35%), expectoration (14%), and hemoptysis (5%). Sixty-one X-rays and 24 CT-scans were performed. On X-rays, an interstitial lung disease was mainly found (77%). On CT-scans, a nodular pattern was predominant (83%): mostly miliary disease (63%), but also excavated nodules (35%). Consolidations were present in 46%, associated with miliary disease in 21%. Thoracic lymphadenopathies were found in 58%, mainly hilar and symmetric (33%). Despite antifungal treatment, case-fatality rate at one month was 22%. Conclusion When faced with an interstitial lung disease on X-rays or a miliary pattern on CT-scans in advanced PLHIV, physicians in endemic areas, apart from tuberculosis or pneumocystosis, should include histoplasmosis as part of their differential diagnoses.

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Prevalence and risk factors of post chikungunya rheumatic musculoskeletal disorders: a prospective follow-up study in French Guiana - Timothée Bonifay; Jean-François Lienne; Cécile Bagoée; Florin Santa; Guillaume Vesin; Gaëlle Walter; Mathieu Nacher; Nathalie Vaserman; Félix Djossou; Loïc Epelboin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)